Jesus and the Laws of Purity : Tradition History and Legal History in Mark 7. - Booth, Roger P. (Library of New Testament studies., 1987)
The principal concern of this book is to show how uncovering the history of legal development can serve as a control for the conclusions of tradition history. In this groundbreaking study, the author brings his own professional experience as a lawyer to bear upon questions of Jewish law and of Gospel criticism. Dr Booth first establishes redaction-critically and form-critically which elements of Mark 7.1-23 are to be assigned to Mark, which to the early church, and which to the probable legal disputes of Jesus with the Pharisees. Then he charts the history of the purity laws, determining which.